2019
DOI: 10.1155/2019/3614960
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Antiaging Effects of Açaí (Euterpe oleracea Mart.) in Mice

Abstract: Depression is a mental disorder that affects 300 million people of all ages worldwide, but fewer than half of those with the condition receive adequate treatment. In addition, the high pharmacological refractoriness (affecting 30%-50% of patients) and toxicity of some classical antidepressants support the pursuit of new therapies. People with this condition show depressed mood, loss of pleasure, high levels of oxidative stress, and accelerated biological aging (decreased telomere length and expression of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…In fact, we found that all Fluvoxamine-treated rats did not show a preference for the use of the left forelimb (unimpaired) in the cylinder test suggesting a reduced toxic effect of the neurotoxin 6-OHDA due to the treatment. This major finding agreed with results from previous studies that showed that antidepressants can reduce MDA levels thereby significantly protecting striatal, prefrontal, and hippocampal cells and preventing neuronal loss associated with both chronic stress and 6-OHDA neurotoxicity [83][84][85][86][87]. We, therefore, postulated that Fluvoxamine possesses antioxidant properties (responsible for mopping up the free radicals generated by the autooxidation of 6-OHDA) and antitoxicity potential that reduced 6-OHDA neurotoxicity.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 90%
“…In fact, we found that all Fluvoxamine-treated rats did not show a preference for the use of the left forelimb (unimpaired) in the cylinder test suggesting a reduced toxic effect of the neurotoxin 6-OHDA due to the treatment. This major finding agreed with results from previous studies that showed that antidepressants can reduce MDA levels thereby significantly protecting striatal, prefrontal, and hippocampal cells and preventing neuronal loss associated with both chronic stress and 6-OHDA neurotoxicity [83][84][85][86][87]. We, therefore, postulated that Fluvoxamine possesses antioxidant properties (responsible for mopping up the free radicals generated by the autooxidation of 6-OHDA) and antitoxicity potential that reduced 6-OHDA neurotoxicity.…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 90%
“…In another study, the effects of Euterpe oleracea juice were studied. The juice was administered over four days to mice treated with lipopolysaccharide to induce a depressive-like behavior [195]. The treatment was capable of reducing despair-like and anhedonic behaviors and showed alterations in electromyographic analysis.…”
Section: Plant Compounds and Longevitymentioning
confidence: 99%
“…Clarified juice of E. oleracea (EO) is available on the international market and is often used as a base for energy drinks [26]. EO already demonstrated a potent neuroprotective effect with conditions as serious as seizures or depression [25,27]. Although initially attributed to its antioxidant properties, both in vitro and in vivo studies revealed that EO is able to act in diverse targets, such the telomerase reverse transcriptase (TERT) mRNA expression [27].…”
Section: Introductionmentioning
confidence: 99%
“…EO already demonstrated a potent neuroprotective effect with conditions as serious as seizures or depression [25,27]. Although initially attributed to its antioxidant properties, both in vitro and in vivo studies revealed that EO is able to act in diverse targets, such the telomerase reverse transcriptase (TERT) mRNA expression [27]. The TERT is the enzyme responsible for telomere length, presently considered as the biological clock in the countdown of the cells’ senescence.…”
Section: Introductionmentioning
confidence: 99%